First report and description of a Cyrilia sp. (Apicomplexa: Haemogregarinidae) from a freshwater Cururu Stingray Potamotrygon cf. histrix (Elasmobranchii: Potamotrygonidae), from the Amazon Region, Brazil - Magro, N. M.; de Oliveira, A. T.; O'Dwyer, L. H. (Wiley, 2016)
A haemogregarine is described in 12 cururu stingray (Potamotrygon cf. histrix), from Mariuá Archipelago, Negro River, in the Brazilian Amazon Basin. All animals, both male and female, were parasitized by the haemogregarine and parasitaemia varied between 0.8% and 10% of erythrocytes. The stages observed included trophozoites or merozoites, suspected meronts, and gamonts presumed to be of two types, macrogamonts and microgamonts. Most stages were observed inside mature erythrocytes, while others were extracellular. The stages observed were most similar to those characteristics of the genus Cyrilia, than to any other fish haemogregarine and may represent a new Cyrilia species.
Keywords: Cyrilia sp.; haemogregarine; haemoparasites; Potamotrygonidae; rays